Analysis of triacylglycerol and phospholipid sn-positional isomers by liquid chromatographic and mass spectrometric methodologies - Fabritius Mikael; Yang Baoru (WILEY, 2025)
Analysis of triacylglycerol (TG) and phospholipid sn-positional isomers can be divided into two main categories: (a) direct separation by chromatography or other means such as ion mobility mass spectrometry and (b) quantification of regioisomer ratios by structurally informative fragment ions with mass spectrometric methods. Due to long retention times and limited performance, researchers are moving away from direct chromatographic separation of isomers, using mass spectrometry instead. Many established analytical methods are targeting specific isomers of interest instead of untargeted analysis of comprehensive profiles of regioisomers. Challenges remain arising from the large number of isobaric and isomeric lipid species in natural samples, often overlapping chromatographically and sharing structurally informative fragment ions. Further, fragmentation of glycerolipids is influenced by the nature of the attached fatty acids, and the lack of available regiopure standards is still an obstacle for establishing calibration curves required for accurate quantification of regioisomers. Additionally, throughput of many methods is still quite limited. Optimization algorithms and fragmentation models are useful especially for analysis of TG regioisomers, as identification using calibration curves alone without proper separation is difficult with complex samples.